Introduction. (July 2021) - Williams, David Lay
This introduction to the review symposium on Ryan Patrick Hanley's works on the relatively neglected early modern philosopher François Fénelon (1651–1715) provides a brief overview of the symposium itself before turning to Hanley's treatment of Fénelon's work on the intersection of politics and religion, culminating in a comparison of Fénelon with his most celebrated admirer, Jean-Jacques Rousseau. The article sketches how both francophone thinkers employ conceptions of divine justice as a measure to counter the dangers of amour-propre, contrasting Fénelon's thick theology with Rousseau's thin theology.